2000
DOI: 10.1108/13552540010323583
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of short‐fibre layered composites: prediction and experiment

Abstract: As a way of enhancing the mechanical properties of photopolymer-based parts produced by layered manufacturing (LM) techniques, the use of short glassfibre reinforcements has been recently explored in the literature. This paper proposes a novel methodology that utilizes a modified rule-of-mixtures model for the prediction of the mechanical properties of such layered composites. The prediction process employs empirical data on (i) the fibre-matrix interface, (ii) the fibres' geometrical arrangement within the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 18 publications
0
25
1
1
Order By: Relevance
“…The mechanical properties of composite material depend on the material properties of the two consistent components of their interface, as well as the amount of reinforcing materials of its geometrical arrangement within the matrix. The amount of reinforcements and their arrangement are determined by the composite fabrication process (Zak et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of composite material depend on the material properties of the two consistent components of their interface, as well as the amount of reinforcing materials of its geometrical arrangement within the matrix. The amount of reinforcements and their arrangement are determined by the composite fabrication process (Zak et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a fiber volume fraction of 20% is the upper limit for this method, due to increased viscosity with increasing fiber content causing issues with the application of thin layers [73]. One way to overcome the high viscosity is to deposit the resin fiber mixture with a nozzle, before going over the deposited layer with a wiping device that smooths the surface [67,74,75]. Figure 10 is an example of the method that has been used with discontinuous fibers, allowing easy deposition of the fiber-doped resin [67].…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…method have yet to be tested [76]. Figure 11 shows the vat photopolymerization composite with the highest strength (72 MPa), formed with special addition of interlayer bonding sites [74]. The idea behind interlayer bonding is that small sections of composite are left uncured, such that when the next layer is deposited, some of the fibers are able to transcend the layer boundary, thus causing better bonding between the layers [74].…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…Enhancing the mechanical properties of photopolymer-based parts produced by layered manufacturing techniques using fibre reinforcements has been recently explored in the literature. Published research work in rapid prototyping has targeted the improvement of the mechanical properties of polymer-based parts produced by layered manufacturing utilizing long and short fibres and even micro-spheres [16][17][18][19][20]. Reported work on rapid prototyping has been focusing on the development of techniques for the fabrication of functional and semi-functional composite parts utilizing direct laser sintering techniques [21].…”
Section: Introductionmentioning
confidence: 99%